Systematization of previous researches of exercises on parallel bars - Velickovic, S.; Paunovic, M.; Vukasinovic, V. (Facta Universitatis: Series Physical Education and Sport, 2016)
Parallel bars is one of the six apparatus of men's artistic gymnastics all- around, based on the great variety of elements performed on this apparatus, as well as of the performing styles and ways of their training. The aim of this paper is to analyze previous studies on parallel bars exercises, and the systematization of research papers related to parallel bars exercises. In code of points (COP) for judging, as many as 168 elements are shown (FIG, 2015) which are performed and which must be performed at competitions on parallel bars. In previous studies there are only 22 elements (13.5%) and they were mainly related to the analysis of the performance techniques of the above mentioned elements. There are no studies dealing with the methodical process of achieving the ideal execution of an element. This only points to the fact that the studies on parallel bars exercises, although conducted over a long period of time, are still in their infancy. Considering the great perspective of elements and the possibility of their upgrade, it is necessary to start with the stuides of elements which are performed through support on the upper arms.